Exploring sound, light, and radiation - Solway, Andrew (New York : Rosen Central, 2008)
An exploration of sound, light, and radiation that explains what they are and discusses the anatomy of a wave, hearing, the science of music, seeing light, color, and more. Includes a glossary and resources.
Traveling in waves -- Anatomy of a wave -- Sound and hearing -- The science of music -- Sight and light -- Bouncing and bending -- Adding color -- Beyond light radiation.
Includes bibliographical references (p. 47) and index.
6.6
5-8
Keywords: Radiation -- Juvenile literature; Vibration -- Juvenile literature; Waves -- Juvenile literature; Radiation; Vibration; Waves; Radiation; Vibration; Waves